Prism adaptation reverses the local processing bias in patients with right temporo-parietal junction lesions. - Bultitude, J; Rafal, R; List, A (2009)
Lesions to the right temporo-parietal cortex commonly result in hemispatial neglect. Lesions to the same area are also associated with hyperattention to local details of a scene and difficulty perceiving the global structure. This local processing bias is an important factor contributing to neglect and may contribute to the higher prevalence of the disorder following right compared with left hemisphere strokes. In recent years, visuomotor adaptation to rightward-shifting prisms has been introduced as a promising treatment for hemispatial neglect. Explanations for these improvements have generally described a leftward realignment of attention, however, the present investigation provides evidence that prism adaptation reduces the local processing bias. Five patients with right temporal-parietal junction lesions were asked to identify the global or local levels of hierarchical figures before and after visuomotor adaptation to rightward-shifting prisms. Prior to prism adaptation the patients had difficulty ignoring the local elements when identifying the global component. Following prism adaptation, however, this pattern was reversed, with greater global interference during local level identification. The results suggest that prism adaptation may improve non-spatially lateralized deficits that contribute to the neglect syndrome.